Preventive maintenance strategy of electric multiple unit critical equipment based on replacement repair - XIONG Lü; LIU Zhilong (机车电传动)
Considering that the entire electric multiple unit (EMU) needs to be withdrawn from service for carrying out preventive maintenance (PM) of the critical equipment, leading to an increase to downtime loss, the concept of replacement repair is proposed in this paper. Specifically, based on the preventive maintenance schedule, the involved critical equipment is replaced with another set of equipment with good performance and then delivered for maintenance, so as to overcome the shortage of sudden increase of service suspension loss caused by preventive maintenance. This paper took the EMU critical equipment as the research object. The preventive maintenance models were built respectively based on replacement repair and non-replacement repair, with the preventive maintenance reliability threshold as the decision making variable, the total maintenance cost of the EMU critical equipment in a replacement cycle as the decision making objective, and applying the 2-level imperfect maintenance measure for the EMU critical equipment. Based on the example analysis, the optimization results of preventive maintenance reliability threshold based on replacement repair are higher than that based on non-replacement repair, and the total maintenance cost of replacement repair is 22.2% lower than that of non-replacement repair. Therefore, the preventive maintenance strategy of the EMU critical equipment based on replacement repair can greatly reduce the total maintenance cost of equipment in a life cycle and can maintain the equipment at a higher reliability level.